Prevalence and predictors of postpartum depression among women attending clinics in Gaborone - Angelina M. Mannathoko; Keneilwe Molebatsi; Deogratias O. Mbuka (South African Journal of Psychiatry)
Background: Untreated postpartum depression (PPD) has the potential to cause significant distress or impairment in functioning with a consequent negative impact on a developing child.